The impact of improvements in medical care resources on homicide trends: the case of germany (1977–2011) - Linde, Antonia (European journal on criminal policy and research, 2018)
This paper addresses whether improvements in healthcare that have taken place since the second half of the twentieth century have contributed to a decrease in the number of homicide victims in Germany. Our study accessed data on healthcare medical resources, mortality, and life expectancy primarily from the World Health Organization (WHO) and the Organisation for Economic Co-operation and Development (OECD) Health Statistics, as well crime data from Interpol’s International Crime Statistics and the European Sourcebook of Crime and Criminal Justice Statistics. The results corroborate the hypothesis when the analysis takes into consideration a time span of more than half a century and remains plausible when it covers the last two decades.